BIOTECHNOLOGY OF THE EXTRACTION OF METALS FROM PERSISTENT SULFIDE ORES OF KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article presents experimental data on bio-oxidation/bio-leaching of sulfide concentrate of the Kumtor gold mining plant with an adapted culture of Acidithiobacillus ferroxidans. The results can be used in the development of biotechnology for extracting gold from deposits in Kyrgyzstan.
Keywords: concentrate, gold, sulfide, pyrite, biological oxidation, biological leaching, microorganisms.